CASHLESS POLICY AND FINANCIAL PERFORMANCE OF DEPOSIT MONEY BANKS (DMBs) IN NIGERIA: A PARSIMONIOUS MODEL APPROACH - James Ayanwale Obadeyi; Kehinde Isiaq Olaiya; Philip Olawale Odewole; Emmanue Olufemi Adebayo (Jurnal Ekonomi dan Bisnis Airlangga, 2026)
Introduction: Challenges such as electronic fraud, customer skepticism, and cybersecurity concerns in Nigeria’s financial sector may undermine the performance of Deposit Money Banks (DMBs), thus warranting an investigation into the effect of the cashless policy on their financial performance. Methods: Using an ex post facto design and purposive sampling over 15 years (2010–2024) with a one-year lag across five banks. Data were sourced from bank financial statements, Central Bank of Nigeria and National Bureau of Statistics, and analyzed employing ordinary least squares (OLS). Results: In the short run, ATM (0.13), mobile banking (1.25), and POS transactions (2.42) positively and significantly influence return on equity (ROE), while internet banking has a negative effect (-1.39) at p<0.05; however, in the long run, all variables exert a positive impact. The series are integrated of order one, I(1), and co-integrated at the 1% and 5% levels, while the parsimonious model explains 61.3% of variations in ROE. Conclusion and suggestion: The cashless policy has mixed short-run effects but positive long-run effects on DMBs’ performance, and recommends that regulators and operators should strengthen policy frameworks to enhance efficient cashless transactions and banking sector performance in Nigeria.